Aging and urban house prices - Norbert Hiller; Oliver W. Lerbs (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
This paper investigates how changes to the age distribution of cities' resident popu-lations shape the growth rate of local house prices in different market segments. For estimation purposes, we combine city-level demographic information with de-tailed housing price data for 87 German cities over 1995-2014. We show that house prices and key demographic variables exhibit strong cross-section dependence but are panel stationary in first differences when this form of dependence is accounted for. Employing a mixed-regressive spatial panel model that incorporates spatial fixed effects as well as changes in city size, purchasing power and mortgage rates, we find that real urban house price appreciation tends to be substantially lower in cities that age more rapidly. Population aging has heterogeneous effects across housing segments: sales price growth of condominiums and single-family homes is negatively related to stronger growth of the old-age dependency ratio, while a posi-tive association is found for aging and real rent growth.
Keywords: G12; J11; R31; 330; House prices; Demographic change; Urban areas; Germany